Macrophages in the cochlea; an immunological link between risk factors and progressive hearing loss - Cunningham, Colm (My University, 2022)
Macrophages are abundant in the cochlea; however, their role in hearing loss is not well understood. Insults to the cochlea, such as noise or insertion of a cochlear implant, cause an inflammatory response, which includes activation of tissue-resident macrophages. Activation is characterized by changes in macrophage morphology, mediator expression, and distribution. Evidence from other organs shows activated macrophages can become primed, whereby subsequent insults cause an elevated inflammatory response. Primed macrophages in brain pathologies respond to circulating inflammatory mediators by disproportionate synthesis of inflammatory mediators. This signaling occurs behind an intact blood–brain barrier, similar to the blood-labyrinth barrier in the cochlea. Local tissue damage can occur as the result of mediator release by activated macrophages. Damage is typically localized; however, if it is to structures with limited ability to repair, such as neurons or hair cells within the cochlea, it is feasible that this contributes to the progressive loss of function seen in hearing loss. We propose that macrophages in the cochlea link risk factors and hearing loss. Injury to the cochlea causes local macrophage activation that typically resolves. However, in susceptible individuals, some macrophages enter a primed state. Once primed, these macrophages can be further activated, as a consequence of circulating inflammatory molecules associated with common co-morbidities. Hypothetically, this would lead to further cochlear damage and loss of hearing. We review the evidence for the role of tissue-resident macrophages in the cochlea and propose that cochlear macrophages contribute to the trajectory of hearing loss and warrant further study.
Keywords: morphology; inflammatory response; Cochlea; Hearing loss; Immune memory; Immune response; Inflammation; Macrophages; Priming